METHODOLOGICAL PREPARATION OF FUTURE TEACHERS OF COMPUTER SCIENCE FOR EXTRA-EDUCATIONAL ACTIVITIES - Salgozha, И.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article deals with the formation of cognitive interest in the subject of informatics, as well as the skills of independent work on the acquisition of new knowledge, the development of thinking, memory, attention. A modern Informatics teacher is called upon not only to educate and educate schoolchildren, to develop students' interest in the subject, which has a great effect in the formation of knowledge and contributes to the activation of the process of knowledge perception and mental activity, but must also be able to organize extracurricular activities. The relevance of this topic meets the new requirements of education in the field of Informatics. The article describes the experience of carrying out extracurricular work in the study of teaching methods of Informatics. Therefore, targeted methodological training of future teachers of informatics for extracurricular work on the subject significantly increases their overall methodological training.